Artificial Intelligence Technologies in Psychology - D.V. Ushakov (Экспериментальная психология)
The article examines the rapidly growing artificial intelligence technologies aimed at understanding and supporting humans. It outlines the main achievements, emerging problems, and promising development paths. It is argued that while these emerging human-oriented artificial intelligence technologies promise a significant increase in psychological comfort, they also pose serious risks. The concept of "digital angels" is proposed—artificial intelligence technologies created to protect the interests of their owner. Digital angels should combine three roles: digital assistants that help individuals organize their lives; digital communicators that ensure connection with other people and the environment; and digital confidants that a person can unconditionally trust.